Towards the concept design of a personal air-land-water vehicle - Arhami, Arhami
This paper describes the approach taken in the current research for creating the conceptual design of a personal air-land-water vehicle. The study relates to the design of a small vehicle that could operate on land, fly in air and move on the surface of water. It emphasizes on the need to understand and having skill of using 3D solid modeling for conceptual engineering design. In this paper, conceptual design refers to the initial design of parts followed by the assemblies to form components of the vehicle. SolidWorks tools have been used to support the design and development of the conceptual design. The results are summarized in the forms of structural model design, dimensions, and possibility of operation.